1981
DOI: 10.1203/00006450-198109000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Single Glomerular Perfusion Rate in Fetal and Newborn Lambs

Abstract: Pediatr. Res. 15: 1248Res. 15: -1255 one can speculate that a decrease in glomerular vascular resistcatheterized fetal lambs between 106 and 140 days of gestation ance is a major determinant in the postnatal increase in glomerular (term, 145 days) and in six newborn lambs between 3 and 19 days perfusion rate and GFR. of age. The present study demonstrates for the first time in lambs that the nephrogenic zone disappears around 130 days of gestation and that the total glomerular counts per kidney in fetuses ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
41
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 30 publications
8
41
0
Order By: Relevance
“…It is well known that maturational changes occur in fetal renal function as term approaches. In both acute and chronic preparations it has been shown that GFR in the ovine fetus increases absolutely with increasing gestational age, but remains constant when expressed as ml/min/g of kidney wt (24)(25)(26)(27). At birth there is a disproportionate increase in GFR (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that maturational changes occur in fetal renal function as term approaches. In both acute and chronic preparations it has been shown that GFR in the ovine fetus increases absolutely with increasing gestational age, but remains constant when expressed as ml/min/g of kidney wt (24)(25)(26)(27). At birth there is a disproportionate increase in GFR (25).…”
Section: Resultsmentioning
confidence: 99%
“…The rat kidney is relatively immature at birth, nephrogenesis not being complete until after birth (23). Nephrogenesis is complete before birth in ovine fetuses (24). Thus glucocorticoid receptors might decrease or be down-regu- The acute effects of a 4-h infusion of cortisol on fetal renal function must be differentiated from the effects of a longer exposure to increased glucocorticoids late in gestation.…”
Section: Resultsmentioning
confidence: 99%
“…The kidney completes nephrogenesis at approximately 130 days gestation in sheep (term 150 days; Robillard et al, 1981) compared with the rat and mouse, in which nephrogenesis continues until 8-10 days after birth (Clark and Bertram, 1999). We subtotally nephrectomized nonpregnant ewes before mating, so that there was a chronic reduction in maternal renal mass for the whole of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…This might be dependent on the duration of compression in the lung or species difference in developmental pattern of the kidney. Nephrogenesis is not completed at birth in rats [10] and pigs [18], while the reverse is true in humans [25], sheep [29] and guinea pigs [31].…”
Section: Discussionmentioning
confidence: 99%